An Exploration of the Trinity Access Mentoring Programme and the Perceptions and Experiences of 6th-year Students in Five of its Post-Primary Link Schools. - Reilly, David (Trinity College Dublin. School of Education. Discipline of Education, 2024)
This research explored the effectiveness of the Trinity Access (TA) mentoring programme in supporting and/or informing the post-school aspirations and expectations of sixth-year students. It assessed the operational aspects of the programme. It also explored how Robert Putnam's bridging and bonding social capital concept helped explain the elements of a positive mentoring relationship. This research was carried out in five TA-linked secondary schools across Dublin. TA mentoring began in 2014 and grew out of a collaboration between the Trinity Access Programme (now known as just Trinity Access) and College for Every Student (an American school outreach programme). The overall TA project includes the delivery of a Postgraduate Certificate in 21st Century Teaching and Learning, alongside workshops in technology-mediated, team-based learning and the development of three other `core practices': Pathways to College, Leadership in Learning and Mentoring. The research design applied was a case study approach using research instruments, such as focus groups and interviews to generate data. Data was generated from five focus groups with five sixth-year students from each of the five schools, interviews with the teachers involved in setting up and running the programme, interviews with ten mentors, one principal, as well as interviews with three staff in TCD. These staff were involved in the development of the programme from the outset, as well as the ongoing operation of the programme. There was also some use of general survey data, which TA had collected on all of their programmes, such as mentoring-related questions which were used prior to data generation. It helped shape the research questions, along with a prior study from O'Sullivan, Mulligan, Kuster, Smith, and Hannon (2017), which recommended further research into mentoring relationships and operations. The approach to data analysis in this study followed Braun and Clarke's (2006; 2018) six steps to carrying out reflexive thematic analysis. Key findings suggested that all parties involved in the programme found it worthwhile but not without its challenges. Logistical and commitment issues led to disjointed organisation over time, as the programme scaled up in numbers of schools and students participating. There was mixed evidence of the programme having an impact on the students' post-school decision-making. It was evident that the decision-making process was multi-faceted, involving a wide range of social, familial and personal factors. Putnam's concept of bridging and bonding social capital theory showed up in the mentoring relationships, but in a slightly different guise. While many factors affected the growth of these relationships, the most common were trust, mutual understanding and commitment (on both sides). Commitment on the mentors' side was a difficulty for the programme as it grew. Findings showed that more structured training, scheduling and commitment, would allow a popular programme for all stakeholders involved, to overcome its logistical challenges. However, scale, whilst desirable at a policy level, may dilute the quality of engagement in the programme.
APPROVED